Constituent year: A new consideration for injury risk in canadian youth ice hockey - Wattie, N.; Cobley, S. P.; Macpherson, A.; Montelpare, W. J.; McKenna, J.; Howard, A.; Baker, J. (Clinical Journal of Sport Medicine, 2010)
The article presents a study which examines whether chronological age within the 2-year age bands of Canadian youth ice hockey players influences the proportion of injury. It states that a retrospective secondary analysis was carried out with the use of data from the Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP) having 4,736 injured players aged 10-15 years old. The result suggests that constituent year may help in determining injury risk.